Patellofemoral kinematics in patellofemoral pain syndrome: The influence of demographic factors. (January 2022) - Fick, Cameron N.; Jiménez-Silva, Rafael; Sheehan, Frances T.; Grant, Camila
Abstract: Due to the multifactorial nature of patellofemoral pain, it is often difficult to identify an individual patient's exact cause of pain. Understanding how demographic variability influences these various factors will support improved consensus in regards to the etiology of PF pain. Thus, in this retrospective study, we tested the hypothesis that sex, height, weight, body mass index (BMI), and age influence the determination of between-groups differences in PF kinematics. We included 41 skeletally mature patients with patellofemoral pain and 79 healthy controls. Three-dimensional patellofemoral kinematics were quantified from dynamic magnet resonance images. We ran multiple regression analyses to determine the influence of demographic covariates (age, sex, height, weight, and BMI) on patellofemoral kinematics. Patellar shift was significantly influenced by weight (p = 0.009) and BMI (p = 0.009). Patellar flexion was influenced by height (p = 0.020) and weight (p = 0.040). Patellar tilt and superior displacement were not influence by demographic variables. Age and sex did not influence kinematics. This study supports the hypothesis that demographic parameters influence PF kinematics. The fact that weight, a modifiable measure, influences both patellar shift and flexion has strong implications for future research and clinical interventions. Clinically, weight loss may have a dual benefit of reducing joint stress and maltracking in patients who are overweight and experiencing patellofemoral pain. The influence of key demographics on patellofemoral kinematics, reinforces the clear need to control for population characteristics in future studies. As such, going forward, improved demographic matching between control and patient cohorts or more advanced statistical techniques that compensate for confounding variables are necessary.